2023
DOI: 10.3390/biomedicines11082114
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-Derived 3D Hepatic Organoids in a Miniaturized Dynamic Culture System

Abstract: The process of identifying and approving a new drug is a time-consuming and expensive procedure. One of the biggest issues to overcome is the risk of hepatotoxicity, which is one of the main reasons for drug withdrawal from the market. While animal models are the gold standard in preclinical drug testing, the translation of results into therapeutic intervention is often ambiguous due to interspecies differences in hepatic metabolism. The discovery of human induced pluripotent stem cells (hiPSCs) and their deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Both hiPSC-aCM lines used for all experiments were derived from healthy donors. In particular, one from a female donor with no diagnosed diseases (https://hpscreg.eu/cell-line/TMOi001-A, purchased from Thermo Fisher Scientific) [71] and the other, previously characterized and published from a 62-year-old male not affected by AF or other cardiac pathologies [72]. hiPSC-aCM lines were maintained on human Biolaminin 521 LN-coated dishes in TeSR-E8™ medium (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hiPSC-aCM lines used for all experiments were derived from healthy donors. In particular, one from a female donor with no diagnosed diseases (https://hpscreg.eu/cell-line/TMOi001-A, purchased from Thermo Fisher Scientific) [71] and the other, previously characterized and published from a 62-year-old male not affected by AF or other cardiac pathologies [72]. hiPSC-aCM lines were maintained on human Biolaminin 521 LN-coated dishes in TeSR-E8™ medium (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…The potential contribution of the NAADP pathway to pacemaker physiology was also explored using genetic tools. Preparations containing the intact spontaneously-beating SAN from wild-type [26] C57BL/6NCrl mice recorded a maximum acceleration of 76% (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83) with an EC50 of 2.7nM (1.9-3.9) in response to Isoprenaline. TPC2 is the lysosomal calcium release channel opened upon NAADP binding [2,3].…”
Section: Lysosomal Calcium Contributes To the β-Adrenergic Response I...mentioning
confidence: 98%
“…A variety of tissue engineering techniques have been investigated to support cells' growth, proliferation, and differentiation into organoids of hepatocytes and cholangiocytes. Three-dimensional cultures based on hydrogels or scaffold matrices prepared from biocompatible materials of natural or semi-synthetic origin provide a biomimetic in a three-dimensional microenvironment for cells to differentiate and organize into functional liver organoids over time [98,99]. To effectively model liver functionality in vitro, it is critical not only to create an inbuilt vasculature, but also to tailor the cellular phenotype by modulating structural properties of the matrix with appropriate stiffness and porosity.…”
Section: Bioengineering Strategies For Growing Liver Organoidsmentioning
confidence: 99%
“…Evidence suggests that human-organoid-based models closely replicate physiological responses to environmental stimuli, allowing for the direct translation and extrapolation of adverse outcomes to humans . For instance, liver organoids serve as a crucial model for studying hepatotoxic responses to external toxicants, given the liver’s central role in metabolizing potential toxins. , In a study by Cheng et al, liver organoids derived from hPSCs were employed to investigate the hepatotoxic effects of polystyrene microplastics . The authors clearly demonstrated that polystyrene microplastics disrupted the function of metabolic enzymes and mitochondria in the liver, exacerbating liver inflammation, thus indicating the impacts on human health .…”
Section: Organoid-based Models In Environmental Toxicologymentioning
confidence: 99%